Network planning for narrow-band power line communication in Smart Grid - Yamnenko, J.S.; Osypenko, K.S.; Neporozhnev, I.V. (Технічна електродинаміка, 2012)
In the paper Smart Grid systems are investigated. Power Line Communication was used as communication technology for Smart Grid. System network planning and main steps of planning process were considered. On the stage of topological design Linear programming was used in order to solve equipment arrangement problem. Results for three different topographies: low, medium and mixed (low+medium voltage) are shown. At network realization Genetic algorithm was used energy-efficient control of electrical devices.